Designing new tools for evaluating gender impacts for climate services in agriculture: Introduction to a series of field experiments in Rwanda - Kramer, Berber; Rose, Alison; Dejene, Samson; Mukangabo, Emerence; Mollerstrom, Johanna; Seymour, Greg; Kagabo, Desire (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Impact evaluations and cost-benefit analyses often guide investments in agricultural development but determining whether an investment is cost effective in empowering women is a major challenge. The multidimensional, dynamic nature of women’s empowerment does not lend itself easily to quantitative measurement and poses challenges for aggregation across different dimensions, and for analyzing trade-offs in development.